Questioning the Validity of Hadith in the Digital Era: Menyoal Validitas Hadits di Era Digital - Desi Asmarita (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The digital era has an influence on understanding information or messages obtained from various social media, including hadith. This requires Muslims to be careful in understanding the validity criteria of hadith. This paper aims to describe the validity of hadith in the digital era, with several important questions; Are there differences in the study of hadith before and after digital tools? Is the study of hadith in the digital era still important?, and how is the analysis of issues related to the validity of hadith in the digital era? The method used in this research is library research with descriptive analysis. Sources of data obtained in the form of books, articles, websites and other reliable documents that are in accordance with the object of research. The results of this study are that: the validity of a hadith in the digital era can be known by referring to the criteria for authentic hadith. The criteria in terms of valid sanad hadith are continuous sanad, fair narrators and dhabit. Meanwhile, in terms of the matan, there are no syadz and 'illat